Kukhar V.V., Suglobov R.V., Prisyazhnyi A.G. The working of design and projecting methodic for technological lubricants spraying system in automatic lines of die-forging and rolling. - Кухарь, В.В.; Суглобов, Р.В.; Присяжный, А.Г. (Problems of Tribology, 2014)
The design of ejecting facility for covering of technological lubricants by spraying on lubricating surfaces was proposed for automatic lines of impression die-forging and rolling. The regulation of modes of stream givens of viscid liquids is possible in knot for lubricants spraying for proportional cover guarantee. The experimental researches were executed and depending between modes of work of spraying system and complex of designing and technological factors was finding. Rational design parameters of ejecting spray system were finding and results grounding to the methodic of calculation of new design of knot for spraying of lubricant in metal forming technologies that realized in automatic lines with counting of pressure in air net, quantity of dismiss of axe of absorbing pipe-line from mixing zone, local resistances of pipe-line from condition of changing of length and square of tube cross-section. The methodic of obtain the designing parameters of ejecting spray system for technological lubricant can be improving by method of successive approximations but example for rolling process was shown about given requiring results at first calculation.